Prioritizing solutions to mitigate abandoned housing projects: Insights from AHP analysis in Malaysia - Nur Farhayu, Ariffin; Saidah An’nisaa, Salam; Mohamad Idris, Ali; Noram Irwan, Ramli; Omar, Jamaludin (Bentham Open, 2024)
Introduction